The internet business book - Ellworth, Jill H. (John Wiley & Sons Inc., 1994)
The Internet Business Book is for businesspeople who want to market their products on the Internet - and when you pick up this book, all you need to know about the Internet is that you want to use it! This book will show you how to get on the Internet and how to put together a complete Internet marketing plan that includes how to choose an Internet service provider that will meet your business's needs; step-by-step instructions for doing online market research, test marketing, advertising, publicity, sales, conferencing, and much more; inside tips on accessing the enormous amount of business information just sitting out there in government, academic, and commercial databases that you can use to get a competitive edge; and how to set up a virtual store and fulfill orders, and deliver services via the Internet worldwide. In addition to the "how-to" information and the listings of hundreds of specific business resources, The Internet Business Book also explains the Internet's rules and customs. Understanding these rules and customs is critical to avoiding damage to your reputation as you do business on the Internet. The reader who picks up The Internet Business Book will find valuable, professional, streetwise advice on how to conduct business on the Internet.